Synthesis, Preparation, and Characterization of Liquid Crystal/Organo-Montmorillonite Nanocomposites - Yanic, Serap Mutlu; Guzeller, Dilek; Ocak, Hale; Cakar, Fatih; Erol, Ismail; Cankurtaran, Ozlem; Eran, Belkis Bilgin (TAYLOR & FRANCIS LTD, 2015)
A new chiral calamitic liquid crystal 4 '-((S)-3,7-dimethyloctyloxy)phenyl 4-(10-undecen-1-yloxy)benzoate (DOPUB) has been synthesized and characterized by spectroscopic methods (H-1-NMR and C-13-NMR). The focus is on the preparation of the nanocomposites of new chiral calamitic liquid crystal DOPUB/Organo-montmorillonite clay (OMMT) by solution intercalation method addition with OMMT contents 2.5, 5, and 7.5 wt% and determination of the morphology, thermal behavior, and crystalline properties of liquid crystal DOPUB/OMMT. Montmorillonite (MMT) modified by cationic surfactant cetyltrimethylammonium bromide (CTAB) for increasing the interaction of clay with DOPUB liquid crystal. The characterization of clay minerals and nanocomposites was investigated by X-ray diffraction. The mesomorphic behavior of liquid crystal (DOPUB) and the nanocomposites was investigated by differential scanning calorimetry (DSC) and optical polarizing microscopy (PM).
Keywords: montmorillonite; nanocomposites; Liquid crystal; BENT-CORE MOLECULES; CRYSTALLINE PHASES; CHIRALITY; Chemistry; Crystallography; Materials Science